Photodocumentation of the Development of Type I Posterior Glottic Stenosis after Intubation Injury - Nelson Scott Howard; Travis L. Shiba; Julianna E. Pesce; Dinesh K. Chhetri (Case Reports in Surgery)
Bilateral vocal fold immobility may result from bilateral recurrent laryngeal nerve paralysis or physiologic insults to the airway such as glottic scars. The progression of mucosal injury to granulation tissue, and then posterior glottis stenosis, is an accepted theory but has not been photodocumented. This paper presents serial images from common postintubation injury to less common posterior glottic stenosis with interarytenoid synechia.